2014
DOI: 10.1182/blood.v124.21.1869.1869
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glutamine Metabolism in Myeloproliferative Neoplasms

Abstract: Introduction: The chronic Philadelphia chromosome negative myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF), are clonal stem cell disorders characterized by unregulated stem cell expansion and overproduction of blood cells. The acquired mutation JAK2V617F plays a central role in the pathogenesis of MPN. Ruxolitinib was the first FDA-approved JAK2 inhibitor for the treatment of MPNs; however, its use is limited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…42 Increased glutamine metabolism was reported in BaF/3 cells expressing VF mutation. 43 It will be interesting to determine whether targeting glutamine metabolism alone or in combination with inhibition of glycolysis can improve therapy for MPNs. A recent study investigated the cell-autonomous metabolic changes in mutant IDH2/JAK2-driven MPNs (present in 2% of MPN patients) and demonstrated that JAK2/IDH-mutant cells are sensitive to an IDH2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…42 Increased glutamine metabolism was reported in BaF/3 cells expressing VF mutation. 43 It will be interesting to determine whether targeting glutamine metabolism alone or in combination with inhibition of glycolysis can improve therapy for MPNs. A recent study investigated the cell-autonomous metabolic changes in mutant IDH2/JAK2-driven MPNs (present in 2% of MPN patients) and demonstrated that JAK2/IDH-mutant cells are sensitive to an IDH2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib was obtained from Jiangsu Hengrui Medicine Co. Purified water was produced by a Milli-Q system (Millipore). [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ] Myristic acid, methoxyamine hydrochloride (purity 98%), alkane solution (C8-C40), and pyridine (99.8% GC) were purchased from Sigma-Aldrich. MSTFA (N-methyl-N-trimethylsilyltrifluoroacetamide) and 1% TMCS (trimethylchlorosilane) were obtained from Pierce Chemical Company.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…9,10 Recent metabolomics studies in oncology found that various types of cancer or different stages of cancer development show different metabolic phenotypes such as aerobic glycolysis (the Warburg effect), one-carbon metabolism and glutaminolysis. [11][12][13] Several biomarkers have been identified in earlier diagnosis, distinguishing various stages of tumor occurrence and progression, as well as biomarkers for treatment response of anticancer drugs. De Petris et al 14 identified different biomarkers of squamous and non-squamous tumors using plasma metabolomics.…”
mentioning
confidence: 99%
“…Among JAK 2 V617F-mutant cells in vitro, as compared with their wild-type counterparts, there has been the observation of increased oxygen consumption, increased extracellular acidification, increased glutamine metabolism, and upregulated glutaminase ( Zhan et al, 2015 ). Glutaminase expression was increased in JAK 2 V617F-mutant peripheral blood CD34 + cells as compared to JAK 2 wild-type progenitor cells from the same patients MPN patients, and its expression increased further with disease progression.…”
Section: Glutaminase Inhibitionmentioning
confidence: 99%
“…Glutaminase expression was increased in JAK 2 V617F-mutant peripheral blood CD34 + cells as compared to JAK 2 wild-type progenitor cells from the same patients MPN patients, and its expression increased further with disease progression. The glutaminase inhibitor, BPTES, along with ruxolitinib, using various laboratory assays, led to an increased anti-proliferative effect among these JAK 2 V617F-mutant cell lines and MPN patient peripheral blood CD34 + cells from MPN patients than that of ruxolitinib alone ( Zhan et al, 2015 ). These observations, along with the knowledge that neoplastic cells generally rely upon aerobic glycolysis more than normal cells do (i.e., Warburg effect), provide the rationale for the clinical investigation of the role of glutaminase inhibitor therapy, with or without JAK inhibition, among MPN patients requiring therapy.…”
Section: Glutaminase Inhibitionmentioning
confidence: 99%